1992
DOI: 10.1084/jem.176.3.835
|View full text |Cite
|
Sign up to set email alerts
|

The CD45 tyrosine phosphatase regulates phosphotyrosine homeostasis and its loss reveals a novel pattern of late T cell receptor-induced Ca2+ oscillations.

Abstract: SummaryCD45 is a transmembrane tyrosine phosphatase implicated in T cell antigen receptor (TCR)-mediated activation. In T cell variants expressing progressively lower levels of CD45 (from normal to undetectable), CD45 expression was inversely related to spontaneous tyrosine phosphorylation of multiple proteins, including the TCR ~" chain, and was directly correlated with TCR-driven phosphoinositide hydrolysis. The Ca 2+ response in these cells was altered in an unexpected fashion. Unlike wild-type ceUs, stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The CD45-negative YAC-1 variant, YACN1 (36), was provided by Jonathan Ashwell, National Institutes of Health, Bethesda, Md.…”
Section: Cellsmentioning
confidence: 99%
“…The CD45-negative YAC-1 variant, YACN1 (36), was provided by Jonathan Ashwell, National Institutes of Health, Bethesda, Md.…”
Section: Cellsmentioning
confidence: 99%
“…It has been demonstrated that CD45 activates src family tyrosine kinase by dephosphorylating the COOH-terminal tyrosine residues on negative regulatory sites of p56 lck [36], or interacts with the z chain [37]. The CD45 ¹ T cell line failed to proliferate and produce IL-2 in response to antigen [38][39][40], but proliferative capacity and IL-2 production were restored after transfection with cDNA encoding CD45 or truncated CD45 that lacked extracellular domains [41][42][43][44]. This indicates that PTPase activity has a key role in the regulatory function of CD45 in transmembrane signalling [45].…”
Section: Discussionmentioning
confidence: 99%
“…In some CD45-cell lines (e.g., Jurkat), baseline tyrosine phosphorylation is normal, but the normal enhancement that usually follows TCR perturbation does not occur (21). In CD45-YAC-1 T cells, there is marked spontaneous tyrosine hyperphosphorylation, but no further increases are induced after TCR cross-linking (44). The reason for the differences between cell lines is unknown but presumably reflects differences in other biologically active molecules that may vary between them.…”
mentioning
confidence: 95%
“…Transformed and spontaneously proliferating T-cell lines that lose CD45 expression no longer manifest increases in phosphatidylinositol hydrolysis or normal rapid increases in [Ca']i when their TCRs are perturbed (22). An atypical Ca2' response is maintained, however, as ligation of TCRs on CD45-T cells results in delayed, asynchronous Ca2+ oscillations due to periodic release of Ca2+ from intracellular stores (44). There are also defects in signaling for tyrosine phosphorylation.…”
mentioning
confidence: 98%
See 1 more Smart Citation